(untitled) (Iraqi Journal of Civil Engineering, 2013)
This work study the effect of partial replacement of cement by hydrated cement on some properties of cement paste and cement mortar such as normal consistency, initial and final setting time, compressive strength, and length change. The results show that pastes containing hydrated cement require more water than reference paste to give normal consistency. The results also show that the replacement by hydrated cement delay the initial and final setting time of cement paste. The delay in setting time increased with increasing the partial replacement by hydrated cement. Compressive strength test was carried out on (54) cubes of (50) mm side dimensions of mortars containing (5, 10, 15, 20, and 25%) of hydrated cement at (3, 7, and 28) days. They were then compared with reference mortar. The compressive strength results show that the compressive strength decreases with increasing the replacement percentage by hydrated cement at all ages. The decreases in compressive strength reached (23.05 %) when (25%) of cement was replaced by hydrated cement in (28) days. The results also show that the replacement of cement by hydrated cement increases the length change of mortars compared with reference mortar.